Intranasal Live Influenza Vaccine Priming Elicits Localized B Cell Responses in Mediastinal Lymph Nodes - Jegaskanda, Sinthujan; Mason, Rosemarie D; Andrews, Sarah F; Wheatley, Adam K; Zhang, Ruijun; Reynoso, Glennys V; Ambrozak, David R; Santos, Celia P; Luke, Catherine J; Matsuoka, Yumiko; Brenchley, Jason M; Hickman, Heather D; et al. (Journal of virology, 2018)
Pandemic live attenuated influenza vaccines (pLAIV) prime subjects for a robust neutralizing antibody response upon subsequent administration of a pandemic inactivated subunit vaccine (pISV). However, a difference was not detected in H5-specific memory B cells in the peripheral blood between pLAIV-primed and unprimed subjects prior to pISV boost. To investigate the mechanism underlying pLAIV priming, we vaccinated groups of 12 African green monkeys (AGMs) with H5N1 pISV or pLAIV alone or H5N1 pLAIV followed by pISV and examined immunity systemically and in local draining lymph nodes (LN). The AGM model recapitulated the serologic observations from clinical studies. Interestingly, H5N1 pLAIV induced robust germinal center B cell responses in the mediastinal LN (MLN). Subsequent boosting with H5N1 pISV drove increases in H5-specific B cells in the axillary LN, spleen, and circulation in H5N1 pLAIV-primed animals. Thus, H5N1 pLAIV primes localized B cell responses in the MLN that are recalled systemically following pISV boost. These data provide mechanistic insights for the generation of robust humoral responses via prime-boost vaccination. We have previously shown that pandemic live attenuated influenza vaccines (pLAIV) prime for a rapid and robust antibody response on subsequent administration of inactivated subunit vaccine (pISV). This is observed even in individuals who had undetectable antibody (Ab) responses following the initial vaccination. To define the mechanistic basis of pLAIV priming, we turned to a nonhuman primate model and performed a detailed analysis of B cell responses in systemic and local lymphoid tissues following prime-boost vaccination with pLAIV and pISV. We show that the nonhuman primate model recapitulates the serologic observations from clinical studies. Further, we found that pLAIVs induced robust germinal center B cell responses in the mediastinal lymph node. Subsequent boosting with pISV in pLAIV-primed animals resulted in detection of B cells in the axillary lymph nodes, spleen, and peripheral blood. We demonstrate that intranasally administered pLAIV elicits a highly localized germinal center B cell response in the mediastinal lymph node that is rapidly recalled following pISV boost into germinal center reactions at numerous distant immune sites.